Pembrolizumab-Induced Psoriasis in Metastatic Melanoma: Activity and Safety of Apremilast, a Case Report - Siciliano, Maria Anna; Dastoli, Stefano; d’Apolito, Maria; Staropoli, Nicoletta; Tassone, Pierfrancesco; Tagliaferri, Pierosandro; Barbieri, Vito (Frontiers in Oncology, 2020)
Background: Immune checkpoint inhibitors targeting CTLA-4, PD-1, and PD-L1 have led to improved survival of metastatic malignant melanoma patients. Due to the mechanism of action, these drugs are associated with a unique toxicity profile. Immune-related adverse events (irAEs) present a wide clinical spectrum and are the Achilles’ heel of immunotherapy. Immunomodulatory drugs are used for the management of irAEs and can theoretically lead to tumor escape. Cutaneous toxicities are among the most commonly irAEs. Case presentation: We report the case of a 75 old years man with metastatic melanoma receiving the anti-PD1 Pembrolizumab. After 10 cycles, he referred to our clinic with itchy psoriatic manifestations spreading >30% of the body surface (12.3 PASI score) that negatively impacted on patient’s quality of life and his compliance to immunotherapy. He had no positive personal history of psoriasis. Given the ineffectiveness of standard treatment and the severity of cutaneous manifestations, in a multidisciplinary approach, Apremilast (an anti-PDE4 oral small molecule) was started. Pembrolizumab was interrupted for 4 weeks until psoriasis improvement of skin lesions and disappearance of itching. Corticosteroid therapy was initiated with immunosuppressive methylprednisolone at a dose of 16 mg/die and the initial dose was progressively reduced until discontinuation. After 10 months, the patient has a good clinical condition with psoriasis complete remission. Moreover, Positron Emission Tomography (PET) and Computed Tomography (CT) scan showed complete response by immune Response Evaluation Criteria in Solid Tumors (iRECIST). Conclusion: Our clinical case is the first report on the safety and efficacy of Apremilast for the treatment of immunotherapy-induced psoriasis in metastatic melanoma.